Evaluating the impact of range walk compensation in delay/Doppler processing over open ocean. Issue 2 (15th July 2021) - Scagliola, Michele; Recchia, Lisa; Maestri, Luca; Giudici, Davide
Abstract: Throughout this paper an analysis is presented on the impact on the geophysical retrievals when a second order correction for the range migration is applied in delay/Doppler processing for Synthetic Aperture Radar altimeters. Under the assumption that the range distance is not varying within a burst acquisition, the range migration is usually corrected in delay/Doppler domain allowing for a great simplification of the processing. Range walk is the changing range migration during the burst acquisition and its compensation can be added to delay/Doppler processing aiming at increasing the accuracy of the Level1b power waveforms. In-house processing framework was exploited to process CryoSat Full Bit Rate products up to the ocean geophysical parameters retrieval with and without compensating for the range walk. Experimental results revealed that, compensating for the range walk, lower Significant Wave Height (SWH) is retrieved so that the existing difference in SWH from delay/Doppler with respect to conventional altimetry can be reduced.